Educational technologies for preventing COVID-19 in preschoolers: An integrative review (Research, Society and Development, 2025)
Objective: to identify and analyze the most used educational technologies to prevent COVID-19 in preschool children. Method: integrative review conducted based on Whittemore and Knafl's steps, with searches in seven databases, with the help of EndNote bibliographic reference manager; The Joanna Briggs model was used to analyze the level of evidence. Results: four articles were selected to compose the final sample, one of which resulted in a booklet and three the creation of digital games. The main outcomes were related to the prevention of COVID-19 and care for disinfecting materials. Conclusion: Studies have shown that the use of gamification as an educational technology for preschool children helps to motivate students and proportionally improve the learning process. The results of this study can contribute to supporting the initiation of new studies on the proposed topic in order to raise awareness among health professionals about the importance of COVID-19 prevention work in schools, also with the preschool population.